Genetics of Bone Mass in Childhood and Adolescence: Effects of Sex and Maturation Interactions. (26th May 2015) - Mitchell, Jonathan A; Chesi, Alessandra; Elci, Okan; McCormack, Shana E; Kalkwarf, Heidi J; Lappe, Joan M; Gilsanz, Vicente; Oberfield, Sharon E; Shepherd, John A; Kelly, Andrea; Zemel, Babette S; Grant, Struan FA
ABSTRACT: We aimed to determine if adult bone mineral density (BMD) susceptibility loci were associated with pediatric bone mass and density, and if sex and pubertal stage influenced any association. We analyzed prospective areal BMD (aBMD) and bone mineral content (BMC) data from the Bone Mineral Density in Childhood Study ( n = 603, European ancestry, 54% female). Linear mixed models were used to assess if 77 single‐nucleotide polymorphisms (SNPs) near known adult BMD susceptibility loci interacted with sex and pubertal stage to influence the aBMD/BMC; adjusting for age, BMI, physical activity, and dietary calcium. The strongest main association was observed between an SNP near C7orf58 and distal radius aBMD. However, this association had a significant sexSNP interaction, revealing a significant association only in females (b = –0.32, p = 1.8 × 10 –6 ). Furthermore, the C12orf23 locus had significant interactions with both sex and pubertal stage, revealing associations in females during Tanner stage I for total hip aBMD (b = 0.24, p = 0.001) and femoral neck aBMD (b = 0.27, p = 3.0 × 10 –5 ). In contrast, the sexSNP interactions for loci near LRP5 and WNT16 uncovered associations that were only in males for total body less head BMC (b = 0.22, p = 4.4 × 10 –4 ) and distal radius aBMD (b = 0.27, p = 0.001), respectively. Furthermore, the LRP5 locus interacted with both sex and pubertal stage, demonstrating associations that were exclusively in males during Tanner V for total hip aBMD (b = 0.29, p = 0.003). In total, significant sexSNP interactions were found at 15 loci; pubertal stageSNP interactions at 23 loci and 19 loci interacted with both sex and pubertal stage. In conclusion, variants originally associated with adult BMD influence bone mass in children of European ancestry, highlighting the fact that many of these loci operate early in life. However, the direction and magnitude of associations for a large number of SNPs only became evident when accounting for sex and maturation. © 2015 American Society for Bone and Mineral Research.